Plasmonic Effect on Performance of Random Lasers - Wan Zakiah Wan Ismail; Irneza Ismail; Sharma Rao Balakrishnan; Mus’ab Sahrim; Jamaludin J.; Dawes, J (American Scientific Publishers, 2024)
Non-Indexed Publication